Long-term risk of neoplastic events after childhood growth hormone treatment: a population-based cohort study in Sweden - Tidblad, Anders; Bottai, Matteo; Smedby, Karin E.; Albertsson-Wikland, Kerstin; Sävendahl, Lars (Frontiers in Endocrinology, 2024)
Background: Increased risk of neoplastic events after recombinant human growth hormone (rhGH) treatment in childhood has been an ongoing concern but long-term safety data are limited.A nationwide population-based cohort study in Sweden of patients treated with rhGH during childhood between 1985-2010, due to isolated growth hormone deficiency (GHD), small for gestational age (SGA) and idiopathic short stature (ISS). The comparison group consisted of 15 age-, sex-, and region-matched controls per patient, randomly selected from the general population. Data on neoplastic events and covariates, such as gestational age, birth weight, birth length, socioeconomic status, and height at study start, were collected through linkage with populationbased registers. The cohort was followed for neoplastic events until the end of 2020.Results: 53,444 individuals (3,408 patients; 50,036 controls) were followed for up to 35 years, with a median follow-up of 19.8 years and a total of 1,050,977 person-years. Patients showed a moderately increased hazard ratio (HR) for neoplastic events overall compared to controls (HR 1.28, 95% CI: 1.12-1.46), but only significant for males (HR 1.39, 95% CI: 1.17-1.66) and not females (HR 1.15, 95% CI: 0.94-1.41). Longer treatment duration was associated with an increased HR, but no association was found between neoplastic events and mean or cumulative dose. No increased risk of malignant neoplasms was observed for the patients compared to matched controls (HR 0.91 95% CI: 0.66-1.26).No association was found between rhGH treatment during childhood for GHD, SGA, or ISS and malignant neoplastic events in early to mid-adulthood. A moderate increase in overall neoplastic events was observed due to an increased number of events in male patients.